AN INVESTIGATION OF TRANSITIVITY SYSTEM IN JUNIOR HIGH SCHOOL STUDENTS' RECOUNT TEXTS: A Case Study of a Public Junior High School in Bandung - Hafiz, Mohammad Reza (2016)
Penelitian berjudul Investigasi Sistem Transitivitas pada Teks Recount Siswa Sekolah Menengah Pertama ini bertujuan untuk meneliti teks recount yang dikembangkan oleh siswa dalam struktur skematik, fitur linguistik, dan kesulitannya, menggunakan sistem transitivity fungsional linguitik yang dikembangkan oleh Halliday (1994). Penelitian ini dilakukan di salah satu Sekolah negeri di Bandung. Enam siswa kelas 8 dipilih sebagai partisipan yang dibagi menjadi tiga kategori; siswa berprestasi tinggi, menengah dan rendah. Penelitian ini menggunakan studi kasus deskripsi kualitatif. Hasil dari penelitian ini menunjukan bahwa teks siswa menerapkan struktur skematik dari teks recount karena teks siswa menerapkan struktur skematik dengan benar pada paragraf yang berbeda. Dalam fitur linguistik, terdapat 3 proses yang yang muncul pada teks siswa kecuali pada teks 5 dimana mental process tidak muncul. material proses menempati jumlah tertinggii pada sebagian teks siswa. Namun, proses yang muncul pada teks siswa yang berprestasi rendah cukup sedikit dan teksnya tidak menunjukan aspek penjelasan yang cukup. Selain itu, banyak teks siswa yang menunjukkan ketidaksamaan dalam penggunaan dari kata kerja bentuk lampau. ---------- This study entitled An investigation of transitivity system in junior high school students' recount texts aims at investigating recount texts developed by the students in terms of its schematic structures and linguistic features and revealing difficulties faced by the students in writing recount texts using transitivity system of functional linguistics developed by Halliday (1994). This study was conducted in one public school in Bandung. Six eighth grade students were selected as the participants divided into three categories; high, middle and low achievers. This study employed a descriptive qualitative case study. The findings showed that all students' texts apply the schematic structure of recount because the texts were arranged correctly in different paragraphs. In terms of linguistic features, there were three types of processes occurring in students' texts except on text 5 where mental processes did not occur. Material processes occupied the highest number in most of the students' texts. However, the processes appeared in low achiever students' texts are limited and the texts did not show many aspects of description. Moreover, most of students' texts showed the inconsistent appearance of past tense.